Solve for c.
ab + c = 5
c = 5/ab
c = 5 - ab
c = 5 + ab

Question

Asked 11/19/2014 8:35:48 AM

Updated 11/19/2014 12:26:42 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

s

chico007hgo|Points 522|

Question

Asked 11/19/2014 8:35:48 AM

Updated 11/19/2014 12:26:42 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Rating

8

ab + c = 5

c = 5 - ab

c = 5 - ab

Added 11/19/2014 12:26:40 PM

This answer has been confirmed as correct and helpful.

Which statement supports the conclusion that dominant genes mask recessive genes?
Genes can be paired in three different combinations.
Genetic information is passed on during reproduction.
A purple flower bred with a white flower produces a purple flower.
Punnett squares are used to visually represent genetic inheritance.

Question

Updated 12/27/2017 1:15:09 PM

1 Answer/Comment

A purple flower bred with a white flower produces a purple flower supports the conclusion that dominant genes mask recessive genes.

Added 12/27/2017 1:15:09 PM

This answer has been confirmed as correct and helpful.

Which of the following supports the argument that animals should be fed more in the winter than in the summer?
Animals expel energy to keep warm.
Feed prices vary throughout the year.
Some vitamins are scarce in winter months.
Carbohydrates provide animals with energy. **Weegy:** The statement "Animals expel energy to keep warm." supports the argument that animals should be fed more in the winter than in the summer. (More)

Question

Expert Answered

Updated 6/28/2020 12:23:23 PM

0 Answers/Comments

Solve for x.
13(x - 3) = 39 **Weegy:** 13(x - 3) = 39 13x - 39 = 39 13x = 39 + 39 13x = 78 x = 78/13 x = 6 **User:** Simplify the given equation.
5x + 2(x - 3) = -2(x - 1)
(More)

Question

Not Answered

Updated 11/19/2014 9:07:22 AM

1 Answer/Comment

5x + 2(x - 3) = -2(x - 1);

5x + 2x - 6 = -2x + 2;

7x - 6 = -2x + 2;

7x + 2x = 2 + 6;

9x = 8;

x = 8/9

5x + 2x - 6 = -2x + 2;

7x - 6 = -2x + 2;

7x + 2x = 2 + 6;

9x = 8;

x = 8/9

Added 11/19/2014 9:07:22 AM

This answer has been confirmed as correct and helpful.

Solve for x.
5(x - 3) + 4(x + 3) = 3(x - 1) **Weegy:** 5(x - 3) + 4(x + 3) = 3(x - 1) 5x - 15 + 4x + 12 = 3x - 3; 5x + 4x - 3x = -3 - 12 + 15; 6x = 0; x = 0 **User:** Solve for x.
7(x - 3) + 3(4 - x) = -8
x = 1/4
x = 25/10
x = -16/19
x = -41/10
**Weegy:**
7(x - 3) + 3(4 - x) = -8;
7x - 21 + 12 - 3x = -8;
4x - 9 = -8;
4x = -8 + 9;
4x = 1;
x = 1/4
**User:** Solve for x.
3(x + 2) + 4(x - 5) = 10
x = 36/7
x = 24/7
x = 16/7
x = 9/7 **Weegy:** 3(x + 2) + 4(x - 5) = 10; 3x + 6 + 4x - 20 = 10; 7x - 14 = 10; 7x = 10 + 14; 7x = 24; x = 24/7 **User:** Simplify the given equation.
6 - (3x + 10) + 4(2 - x) = 15
4 - 7x = 15
4 - 4x = 15
12 - 7x = 15 **Weegy:**
6 - (3x + 10) + 4(2 - x) = 15;
6 - 3x - 10 + 8 - 4x = 15;
6 - 7x - 2 = 15;
-7x + 4 = 15;
-7x = 15 - 4;
-7x = 11;
x = -11/7
**User:** Solve for x.
8(x + 1) - 3(x + 4) = 7(2 - x) (More)

Question

Updated 11/19/2014 10:32:51 AM

1 Answer/Comment

8(x + 1) - 3(x + 4) = 7(2 - x);

8x + 8 - 3x - 12 = 14 - 7x;

5x - 4 = 14 - 7x;

5x + 7x = 14 + 4;

12x = 18;

x = 18/12;

x = 3/2

8x + 8 - 3x - 12 = 14 - 7x;

5x - 4 = 14 - 7x;

5x + 7x = 14 + 4;

12x = 18;

x = 18/12;

x = 3/2

Added 11/19/2014 10:32:51 AM

This answer has been confirmed as correct and helpful.

34,469,115

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 842 [Total 6715] Ratings 19 Comments 652 Invitations 0 Online

There are no comments.